The impact of Philosophy for Children (P4C) activities on enhancing the speaking skills of gifted students - Balcı, Emine; Eryılmaz, Ramazan (Frontiers in Psychology, 2024)
The aim of this study was to investigate the impact of Philosophy for Children (P4C) activities integrated into Turkish lessons on the speaking skills of gifted students. Both quantitative and qualitative data were collected through interviews and various scales, employing a mixed-method design. The results indicated that students had positive feelings about P4C, including appreciation, curiosity, surprise, excitement, self-confidence, and empathy. They believed that P4C enhanced their problem-solving, creativity, questioning, effective speaking, and collaboration skills. However, some students also expressed negative views, tough less frequently, citing issues such as nonsense, limited time, the necessity of prior knowledge, and lack of idea diversification. Quantitative data revealed that P4C activities significantly improved the speaking skills of gifted students and notably reduced their speaking anxiety. Additionally, sex and program variables showed no significant effect on speaking skills and speaking anxiety.